The Effect of Demographic factors on Job Stress: A Comparative Study of Public and Private Life Insurance Sector (International Journal of Scientific Research and Management (IJSRM), 2017)
Job stress is a very common phenomenon in almost every organization. Some of the jobs are more stressful than others, as some can take it as a challenge and other may face excessive pressures while handling it. Every employee is different from one another in terms of knowledge, skills, ability and experience in handing situations. The purpose of the study is to identify the correlation of stress among the employees of public (LIC of India) and private (ICICI Prudential) life insurance sectors in Rajasthan in accordance with their demographic profile. Structured questionnaires were used to gather data from 200 employees each from public as well as private life insurance companies from five cities of Rajasthan i.e. Jaipur, Jodhpur, Alwar, Bikaner and Udaipur. The data was collected using Likert scale. The association of demographic factors, viz., age, designation, monthly income and no. of dependents of the respondents on various dimensions of job stressors was examined through chi-square test. There are five categories considered for job stress which are working aspects, training and benefits, motivational tools, performance evaluation and appraisal and job satisfaction.